Population structure of the mosquito Aedes aegypti (Stegomyia aegypti) in Pakistan. Issue 4 (12th May 2013) - RASHEED, S. B.; BOOTS, M.; FRANTZ, A. C.; BUTLIN, R. K.
Abstract : Eleven microsatellite markers were used to determine the genetic population structure and spread of Aedes aegypti ( Stegomyia aegypti ) (Diptera: Culicidae) in Pakistan using mosquitoes collected from 13 different cities. There is a single genetic cluster of Ae. aegypti in Pakistan with a pattern of isolation by distance within the population. The low level of isolation by distance suggests the long‐range passive dispersal of this mosquito, which may be facilitated by the tyre trade in Pakistan. A decrease in genetic diversity from south to north suggests a recent spread of this mosquito from Karachi. A strong negative correlation between genetic distance and the quality of road connections shows that populations in cities connected by better road networks are less differentiated, which suggests the human‐aided passive dispersal of Ae. aegypti in Pakistan. Dispersal on a large spatial scale may facilitate the strategy of introducing transgenic Ae. aegypti or intracellular bacteria such as Wolbachia to control the spread of dengue disease in Pakistan, but it also emphasizes the need for simple measures to control container breeding sites.